A study on the influence of Human Resource Management (HRM) practices towards employee performance at Tesco Bandar Sungai Petani, Kedah / Nur Farahani Rosedi and Nur Najmina Nisrin Mat Jaafar - Rosedi, Nur Farahani; Mat Jaafar, Najmina Nisrin (2018)
Hypermarket retailing spend millions every year in recruiting, training, compensating, encouraging and inspiring their employees to perform well in order to increase the level of profits of the company. This is because the success of an organization largely depends on performance of employees. Thus, this study was conducted to examine the influence of Human Resource Management (HRM) practices towards employee performance. A questionnaire was developed and a pilot test was done to test the normality, reliability and validity of the scale. The independent variables to measure Human Resource Management (HRM) practices include training, career development, rewards and employees’ involvement. The dependent variable used in this study is employee performance. The collected data was analysed using descriptive means and Pearson Product-Moment Correlation via SPSS Version 24. This study found that three Human Resource Management (HRM) practices such as training, career development and rewards have no significant with employee performance. Thus, the future studies may compare different Human Resource Management (HRM) practices in different hypermarket in Malaysia that can influences towards employee performance.